THE EFFECT OF SCRIPTED SONG-BASED AUDIO MEDIA ON ENGLISH COMPETENCY OF THE FIFTH GRADE STUDENTS OF PRIMARY SCHOOL IN TEJAKULA SUB-DISTRICT 1 IN ACADEMIC YEAR 2014/2015 - ., I Gede Angga Pradipta Saputra; ., Dra.Ni Made Ratminingsih, MA; ., Dra. Luh Putu Artini, MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This experimental study aimed at finding out the significant effect of Scripted Song-based Audio Media towards English competency of the fifth grade students of SD Negeri 1 Tejakula in academic year 2014/2015. The design of this study was post-test only control group design. Random sampling technique was employed in order to define which class selected as control group or experimental group, resulted in class 5 of SDN 2 Tejakula randomly selected as the control group which was taught by using conventional teaching media and class SDN 1 Tejakula randomly selected as the experimental group which was taught by using Scripted Song-based Audio Media. Both groups consisted of 20 students each. The results of data analysis showed that the students who were taught by implementing Scripted Song-based Audio Media performed better than those who were taught by implementing conventional teaching media. The descriptive statistic analysis result of mean score of listening post-test in experimental group was 79, while in control group was 68. The mean score of speaking post-test in experimental group was 81 and in the control group was 70. In reading, the mean score in experimental group was 78.2 while in the control group was 68.7. The mean score of writing post-test 90.4 for experimental group and 76.1 for control group. The mean score of English competency in experimental group was 80.9 while the control group was 71.1. The results of t-test analysis of the tobs was 6.256. It was higher than the value of the tcv at 2.024394164(α = 0.05). Moreover, the result of observation indicated that the implementation of Scripted Song-based Audio Media motivated the students in comprehending English competence. In conclusion, Scripted Song-based audio media contributed in giving a significant effect to students’ English competency. keyword : English competency, Scripted songs